Thirty-Day Clinical Outcome of Primary Percutaneous Intervention Versus Fibrinolysis Followed by Coronary Angiography in ST-Segment Elevation Myocardial Infarction - Oon, Y.Y.; Yakub, N; Ramli, S.A.S; Koh, K.T.; Ho, K.H.; Shu, F.; Tan, C.T.; Voon, C.Y.; Khiew, N.Z.; Said, A.; Mohd Amin, N.H.; Cham, Y.L. (Elsevier, 2017)
Background: Primary percutaneous coronary intervention (PCI)is the preferred reperfusion strategy in patients with ST-segment elevation myocardial infarction (STEMI). However, timely PCI cannot be offered to many patients. Objective: The purpose of this study was to compare the 30-day clinical outcome of primary PCI strategy and fibrinolysis followed by coronary angiography strategy in STEMI patients. Methods: This was a prospective, observational, single center study. All patients admitted for STEMI from 1 January 2016 to 30 November 2016 were screened for the study. Patients were divided into 2 reperfusion strategies: primary PCI or fibrinolysis followed by coronary angiography. Primary outcome was composite of all-cause mortality at 30 days. Results: A total of 178 patients were identified: 33 (18.5%) underwent primary PCI and 145 (81.5%) underwent fibrinolysis first. The median door-to-balloon time in the primary PCI group was 161.0 minutes (IQR 84.5). The median time from fibrinolysis-to-arrival at catheterization lab was 1738 minutes (IQR 901). The median total ischaemic time was 369 min (IQR 524) and 210 (IQR 247) for the primary PCI and fibrinolysis first group respectively (p=0.002). Kaplan-Meier survival analysis for 30-day all-cause mortality was 24.2% vs 9.7% respectively in primary PCI and fibrinolysis group p=0.018). Multivariate Linear Regression showed that Killip Class and LVEF were independent predictors of 30-day all-cause mortality. Reperfusion strategy was not associated with 30-day all-cause mortality (p=0.216). Conclusions: The clinical outcome of primary PCI strategy in STEMI is not better than fibrinolysis followed by coronary angiography strategy when timely PCI cannot be performed.